Effect of iron fortification on anaemia and risk of malaria among Ghanaian pre-school children with haemoglobinopathies and different ABO blood groups - Samuel Kofi Tchum; Samuel Asamoah Sakyi; Fareed Arthur; Bright Adu; Latifatu Alhassan Abubakar; Felix Boakye Oppong; Francis Dzabeng; Benjamin Amoani; Thomas Gyan; Kwaku Poku Asante (BMC Nutrition, 2023)
Abstract Background Haemoglobinopathies such as sickle cell disorder and glucose-6-phosphate dehydrogenase (G6PD) deficiency as well as differences in ABO blood groups have been shown to influence the risk of malaria and/or anaemia in malaria-endemic areas. This study assessed the effect of adding MNP containing iron to home-made weaning meals on anaemia and the risk of malaria in Ghanaian pre-school children with haemoglobinopathies and different ABO blood groups. Methods This study was a double-blind, randomly clustered trial conducted within six months among infants and young children aged 6 to 35 months in rural Ghana (775 clusters, n = 860). Participants were randomly selected into clusters to receive daily semiliquid home-prepared meals mixed with either micronutrient powder without iron (noniron group) or with iron (iron group; 12.5 mg of iron daily) for 5 months. Malaria infection was detected by microscopy, blood haemoglobin (Hb) levels were measured with a HemoCue Hb analyzer, the reversed ABO blood grouping microtube assay was performed, and genotyping was performed by PCR–RFLP analysis. Results The prevalence of G6PD deficiency among the study participants was 11.2%. However, the prevalence of G6PD deficiency in hemizygous males (8.5%) was significantly higher than that in homozygous females (2.7%) (p = 0.005). The prevalence rates of sickle cell traits (HbAS and HbSC) and sickle cell disorder (HbSS) were 17.5% and 0.5%, respectively. Blood group O was dominant (41.4%), followed by blood group A (29.6%) and blood group B (23.3%), while blood group AB (5.7%) had the least frequency among the study participants. We observed that children on an iron supplement with HbAS had significantly moderate anaemia at the endline (EL) compared to the baseline level (BL) (p = 0.004). However, subjects with HbAS and HbAC and blood groups A and O in the iron group had a significantly increased number of malaria episodes at EL than at BL (p < 0.05). Furthermore, children in the iron group with HbSS (p < 0.001) and the noniron group with HbCC (p = 0.010) were significantly less likely to develop malaria. Conclusions Iron supplementation increased anaemia in children with HbAS genotypes and provided less protection against malaria in children with HbAC and AS and blood groups A and O. Trial registration clinicaltrials.gov Identifier: NCT01001871 . Registered 27/10/2009. Registration number: https://clinicaltrials.gov/ct2/show/record/NCT01001871 .